"Si vir es": Palabras de mujer e identidad masculina en Livio AUC 1 (Argos, 2025)
The surprising presence of women in Ab urbe condita 1 can be observed in the remarkable and unusual accumulation of female figures that take part in an active way in the events narrated and in the frequency in which they generate male interlocutor dialogic situations with persuasive aims.The study of this situations demonstrates that this is a resource employed to form, either by similarity or contrast, the identity of the elite Roman man.
Keywords: Livy; speech; woman; man; identity